Intracellular Itinerary of Internalised β‐Secretase, BACE1, and Its Potential Impact on β‐Amyloid Peptide Biogenesis. (8th July 2013) - Chia, Pei Zhi Cheryl; Toh, Wei Hong; Sharples, Robyn; Gasnereau, Isabelle; Hill, Andrew F.; Gleeson, Paul A.
Abstract : BACE1 cleavage of the amyloid precursor protein (APP) is the initial step in the formation of the amyloidogenic Aβ peptide. This article reports that cell surface BACE1 is internalised by the AP2/clathrin‐dependent pathway and traffics to early endosomes then recycling endosomes. In contrast, internalised wild‐type APP traffics to late endosomes/lysosomes. A BACE/TGN38 chimera that recycles via the TGN is more efficient in Aβ production than wild‐type BACE1 indicating that the recycling itinerary of BACE1 influences Aβ biogenesis. Abstract : β‐Secretase (BACE1) cleavage of the amyloid precursor protein (APP) represents the initial step in the formation of the Alzheimer's disease associated amyloidogenic Aβ peptide. Substantive evidence indicates that APP processing by BACE1 is dependent on intracellular sorting of this enzyme. Nonetheless, knowledge of the intracellular trafficking pathway of internalised BACE1 remains in doubt. Here we show that cell surface BACE1 is rapidly internalised by the AP2/clathrin dependent pathway in transfected cells and traffics to early endosomes and Rab11‐positive, juxtanuclear recycling endosomes, with very little transported to the TGN as has been previously suggested. Moreover, BACE1 is predominantly localised to the early and recycling endosome compartments in different cell types, including neuronal cells. In contrast, the majority of internalised wild‐type APP traffics to late endosomes/lysosomes. To explore the relevance of the itinerary of BACE1 on APP processing, we generated a BACE1 chimera containing the cytoplasmic tail of TGN38 (BACE/TGN38), which cycles between the cell surface and TGN in an AP2‐dependent manner. Wild‐type BACE1 is less efficient in Aβ production than the BACE/TGN38 chimera, highlighting the relevance of the itinerary of BACE1 on APP processing. Overall the data suggests that internalised BACE1 and APP diverge at early endosomes and that Aβ biogenesis is regulated in part by the recycling itinerary of BACE1.